No heaven but no longer hell? Tales of criminal victimization and shelter among irregular migrant men - De La Maza Díaz, José Miguel (International review of victimology, 2024)
Irregular migrants are legally excluded from formal employment, regular housing markets, and unemployment benefits, and in the Netherlands, they are also excluded from governmentally funded homeless shelters. While alternative sheltering arrangements have emerged for specific irregular migrants (e.g. minors, victims of human trafficking), unaccompanied adult men were typically still excluded from institutionalized shelter. In 2019, however, the national government launched a sheltering pilot for irregular migrants, which involves unaccompanied adult men in particular. Based on qualitative fieldwork in Rotterdam, and using Van Dijk and Steinmetz’s risk model as a theoretical lens, we argue that irregular status, interacting with other relevant factors such as social capital, co-determines the men’s criminal victimization risks, and fear of crime. In addition, we show how access to shelter changed the meaning and therefore the consequences of irregular status, resulting in both ‘de-marginalization’ and ‘re-marginalization’: victimization risks were generally reported to be lower in the shelter than in the streets, but sheltering also introduced new risks, which were mostly attributed to the co-presence of other sheltered groups, especially marginalized European Union (EU) citizens with a stronger immigration status. Paying attention to immigration statuses, and how they are socially constructed, thus helps to shed light on contemporary criminal victimization risks.